2007
DOI: 10.1136/pgmj.2006.049023
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma pneumoniae and its role in asthma

Abstract: Mycoplasma pneumoniae (M pneumoniae), primarily recognised as a causative agent of community-acquired pneumonia has recently been linked to asthma. An infection with M pneumoniae may precede the onset of asthma or exacerbate asthma symptoms. Chronic infection with M pneumoniae has been suspected to play a part in some patients with asthma. The role of immunoglobulin E-related hypersensitivity and induction of T helper type 2 immune response leading to inflammatory response in M pneumoniae-infected patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 40 publications
(41 reference statements)
3
48
1
4
Order By: Relevance
“…Interestingly, 44.4% of the patients suffered from asthma along with M. pneumoniae respiratory infection. Waites and Talkington and Nisar et al reported that M. pneumoniae infection may be related to asthma (10,20). Smoking is globally related with pulmonary diseases (21), but the results of this study did not show any significant rise in M. pneumoniae infection among cigarette smokers (P = 0.3).…”
Section: Discussioncontrasting
confidence: 55%
“…Interestingly, 44.4% of the patients suffered from asthma along with M. pneumoniae respiratory infection. Waites and Talkington and Nisar et al reported that M. pneumoniae infection may be related to asthma (10,20). Smoking is globally related with pulmonary diseases (21), but the results of this study did not show any significant rise in M. pneumoniae infection among cigarette smokers (P = 0.3).…”
Section: Discussioncontrasting
confidence: 55%
“…However, we also observed a significant increase in eosinophilic infiltration in BALF samples from P-130-vaccinated and challenged mice (one animal from this group had 64% eosinophils in the differential leukocyte count). Such eosinophilia resembles that found in allergic asthma, consistent with reports that M. pneumoniae exacerbates atopy in asthmatic patients (reviewed by Nisar et al (30). Unfortunately, few reports have studied the influx of eosinophils during M. pneumoniae infection (particularly in acute models of infection), but Chu et al (6) found no evidence of eosinophils in rechallenged BALB/c mice 3 days postinfection (which also exhibited exacerbated disease).…”
Section: Discussionsupporting
confidence: 65%
“…Although M. pneumoniae is a well established cause of asthma exacerbations, more recent data have suggested that it may also contribute to the pathogenesis of asthma (7)(8)(9)(10)(11)(12). The lipoprotein constituents of M. pneumoniae membrane play a critical role in immune recognition by the host and induction of the inflammatory response (13,14).…”
mentioning
confidence: 99%